Design, fabrication and testing of a low cost green house - GOVINDAN S; Jenet P. V; Jissy K. Jacob; Manoj Kumar T. S; Dr. Jobi V. Paul (Guide) (Tavanur 1993 Department of Land Water Resources and Conservation Engineering)
Design, fabrication and testing of a low cost green house
Design, fabrication and testing of a low cost green house